Evaluasi Usability dengan Metode Heuristic Walkthrough (Studi Kasus: Website Beasiswa XYZ) - Muhammad Ilham Maksum; Buce Trias Hanggara; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The xyz scholarship website is a site developed for xyz scholarship recipients, a scholarship program organized by the xyz institution. The purpose of this site is to facilitate the management in monitoring, as well as to facilitate scholarship recipients in reporting. Then, from the user experience questionnaire (UEQ) that the researcher distributed to eleven respondents, the score for the newness scale of the xyz scholarship website was on an average of 0.31 and a comparison benchmark that was "below average". Heuristic walkthrough is a combination of cognitive walkthrough evaluation method and heuristic evaluation. Cognitive walkthrough is an evaluation method used by all evaluators by carrying out evaluation tasks and helping with thought provoking questions to find problems. Next, heuristic evaluation is a method used by experts by comparing websites based on Nielsen's heuristic principles and giving a severity rating for each problem. This evaluation involves three categories of evaluators, namely novice, regular expert, and double expert. The results of the cognitive walkthrough evaluation found one hundred and two problem findings and 60.78% of them had similarities with the findings on the heuristic evaluation. Meanwhile, heuristic evaluation resulted in twenty problem findings with the highest severity rating of 2.35 on the H-5 (Error prevention). Taking into account the evaluation results, there are 24 suggestions for improvement with details, eighteen suggestions for interface improvements or including systems, four for system fixes, and two without improvements.